DAMPAK PENDIDIKAN KESEHATAN MEDIA AUDIOVISUAL TERHADAP TINGKAT PENGETAHUAN IBU HAMIL DENGAN HYPEREMESIS GRAVIDARUM - Margaretta, Sheylla; Gayatri, Paramita Ratna (LPPM STIKes SATRIA BHAKTI NGANJUK, 2023)
Physiological adaptations of the body in the process of pregnancy, one of which is the gastrointestinal system. Complaints of nausea and vomiting in the early trimester of pregnancy are normal things, but if they occur excessively it will affect the general condition of pregnant women. This situation is called hyperemesis gravidarum, which is a state of nausea and vomiting more than 10 times / day in pregnant women which will result in dehydration, weight loss, changes in body electrolytes, activity disturbances and also fetal distress. This study aims to determine whether or not there is an impact of audiovisual media health education on the level of knowledge of pregnant women with hyperemesis gravidarum.